Zone of teacher promoted action based on gender in math lesson - Nadrah Afiati Nasution; Nurhasanah Siregar; Imelda Wardani Br. Rambe; Erminawaty Simanjuntak (AXIOM : Jurnal Pendidikan dan Matematika, 2024)
This study was conducted to understand the Zone of Promoted Action (ZPA) of teachers in the context of mathematics learning, based on gender. This research is a descriptive exploratory study using a qualitative approach. The data analysis techniques employed in this study include data transcription, data checking, data reduction, data credibility, and conclusion drawing. The subjects of this study are pre-service PPG students who are prospective teachers. The instruments used in this study include questionnaires and observation sheets. Based on the results of the study, it can be concluded that each teacher, regardless of gender background, possesses unique ZPA capabilities characterized by their ability to manage time, guide discussions, and focus students on the material.